A framework for interactive human–robot design exploration. (September 2020) - Jensen, Mads Brath; Foged, Isak Worre; Andersen, Hans Jørgen
This study seeks to identify key aspects for increased integration of interactive robotics within the creative design process. Through its character as foundational research, the study aims to contribute to the advancement of new explorative design methods to support architects in their exploration of fabrication and assembly of an integrated performance-driven architecture. The article describes and investigates a proposed design framework for supporting an interactive human–robot design process. The proposed framework is examined through a 3-week architectural studio, with university master students exploring the design of a brick construction with the support of an interactive robotic platform. Evaluation of the proposed framework was done by triangulation of the authors' qualitative user observations, quantitative logging of the students' individual design processes, and through questionnaires completed after finishing the studies. The result suggests that interactive human–robot fabrication is a relevant mode of design with positive effect on the process of creative design exploration.